Energy and exergy analysis of compact automotive air conditioning (AAC) system - M. Z., Farid; Azmi, W. H.; Zawawi, N. M. M.; R., Mamat; A. I. M., Shaiful (IOP Publishing, 2019)
Automotive Air conditioning (AAC) is a unit that uses a high measure of energy from a car total engine power. In equatorial climate country such as Malaysia, high usage of AAC is inevitable due to hot, humid and rainy weather throughout the year. An understanding about the energy and exergy losses is essential to find the potential improvement to maximise the efficiency in an AAC system. The main objective of this study is to study the performance of energy and the exergy of a compact automotive air conditioning system. This cycle uses R134a and PAG lubricant as the working fluid. The different ranges of initial refrigerant charge and compressor speed have been tested on the AAC to evaluate the effect of different major thermodynamic parameters in performance. A theoretical model is developed to work out the thermodynamic parameters such as coefficient of performance, exergy destruction ratio, component efficiency defect as well as the dimensionless exergy balance for the AAC system components. The results of this study have shown that most of the energy has been destructed in evaporator part. In order to maximize the efficiency and performance of AAC system, further optimization needs to be done in order to improve the evaporator component.